Vulnerability of Bangladesh to Cyclones in a Changing Climate : Potential Damages and Adaptation Cost - Dasgupta, Susmita; Huq, Mainul; Khan, Zahirul Huq; Ahmed, Manjur Murshed Zahid; Mukherjee, Nandan; Khan, Malik Fida; Pandey, Kiran (2012)
This paper integrates information on climate change, hydrodynamic models, and geographic overlays to assess the vulnerability of coastal areas in Bangladesh to larger storm surges and sea-level rise by 2050. The approach identifies polders (diked areas), coastal populations, settlements, infrastructure, and economic activity at risk of inundation, and estimates the cost of damage versus the cost of several adaptation measures. A 27-centimeter sea-level rise and 10 percent intensification of wind speed from global warming suggests the vulnerable zone increases in size by 69 percent given a +3-meter inundation depth and by 14 percent given a +1-meter inundation depth. At present, Bangladesh has 123 polders, an early warning and evacuation system, and more than 2,400 emergency shelters to protect coastal inhabitants from tidal waves and storm surges. However, in a changing climate, it is estimated that 59 of the 123 polders would be overtopped during storm surges and another 5,500 cyclone shelters (each with the capacity of 1,600 people) to safeguard the population would be needed. Investments including strengthening polders, foreshore afforestation, additional multi-purpose cyclone shelters, cyclone-resistant private housing, and further strengthening of the early warning and evacuation system would cost more than $2.4 billion with an annual recurrent cost of more than $50 million. However, a conservative damage estimate suggests that the incremental cost of adapting to these climate change related risks by 2050 is small compared with the potential damage in the absence of adaptation measures.